A zirconium-based metal–organic framework sensitized by thioflavin-T for sensitive photoelectrochemical detection of C-reactive protein. Issue 72 (21st August 2019) - Li, Meng-Jie; Wang, Hai-Jun; Yuan, Ruo; Chai, Ya-Qin
Abstract : Herein, a photoelectrochemical (PEC) assay was proposed for sensitive detection of C-reactive protein (CRP) based on zirconium-based metal-organic framework (PCN-777) as the photoelectric material and thioflavine-T (Th-T) as the sensitizer. Abstract : Herein, a novel photoelectrochemical (PEC) assay was developed for the sensitive detection of C-reactive protein (CRP) based on a zirconium-based metal–organic framework (PCN-777) as the photoelectric material and thioflavin-T (Th-T) as the effective signal sensitizer coupled with rolling circle amplification (RCA).